Exploring Phytochemicals for Combating Antibiotic Resistance in Microbial Pathogens - Khare, Tushar; Anand, Uttpal; Dey, Abhijit; Assaraf, Yehuda G.; Chen, Zhe-Sheng; Liu, Zhijun; Kumar, Vinay (Frontiers in Pharmacology, 2021)
Microbial drug resistance is emerging as a serious threat to human healthcare globally and the multidrug-resistant (MDR) strains are imposing major hurdles to the progression of drug discovery programs. Newer drug resistance mechanisms in microbes contribute to the inefficacy of the existing drugs, prolonged illness and escalating expenditures. The injudicious usage of the conventional and commonly available antibiotics in human health, hygiene, veterinary and agricultural practices is proving to be a major driver for evolution, persistence and spread of drug-resistance at a frightening rate. The drying pipeline of new and potent antibiotics is adding to the severity. Therefore, novel and effective new drugs and innovative therapies to treat MDR infections are urgently needed. Apart from the different natural and synthetic drugs being tested, plant secondary metabolites or phytochemicals are proving efficient in combating the drug-resistant strains. Various phytochemicals from classes including alkaloids, phenols, coumarins, terpenes have been successfully demonstrated their inhibitory potential against the drug-resistant pathogens. Several phytochemicals have proved effective against the molecular determinants responsible for attaining the drug resistance in pathogens like membrane proteins, biofilms, efflux pumps and bacterial cell communications. However, translational success rate needs to be improved, but the trends are encouraging. This review highlights current knowledge and developments, associated challenges and future prospects for the successful application of phytochemicals in combating the drug-resistant pathogens.